COMPUTER METHODS IN LITERARY STUDIES: USING ARTIFICIAL INTELLIGENCE, BIG DATA, AND ALGORITHMIC APPROACHES FOR TEXT ANALYSIS - Kadirova M. X. (Modern American Journals, 2025)
The article explores the transformative impact of computer-based methods on literary studies, with a focus on the combined use of artificial intelligence (AI), big data processing, and algorithmic modelling for in-depth analysis and interpretation of literary texts with unprecedented depth and scale.
Keywords: Digital literary analysis, machine learning, natural language processing, distant reading, stylometric profiling, thematic clustering, semantic embeddings, computational humanities.